Efektivitas Belanja Perjalanan Dinas dan Dukungan Organisasi dalam Menunjang Kinerja Pegawai Badan Pengawas Pemilihan Umum Provinsi Sumatera Barat - Efli Letsunanda Bikuraini; Riri Mayliza (YASIN, 2026)
Although public-sector employee performance is an important factor in supporting the effectiveness of institutional task implementation, studies that specifically examine the influence of the effectiveness of official travel expenditure and perceived organizational support on employee performance at the General Election Supervisory Agency (BAWASLU) of West Sumatra Province still need to be strengthened. This study aims to analyze the influence of the effectiveness of official travel expenditure and perceived organizational support on the performance of employees of BAWASLU of West Sumatra Province. This study used a quantitative approach with a causal associative design. The study population included all 67 employees of BAWASLU of West Sumatra Province, using a saturated sampling or census technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS. The results showed that the effectiveness of official travel expenditure had a positive and significant effect on employee performance, with a calculated t-value of 3.153 and a significance value of 0.003. Perceived organizational support also had a positive and significant effect on employee performance, with a calculated t-value of 4.257 and a significance value of 0.000. The Adjusted R Square value of 0.494 indicates that the effectiveness of official travel expenditure and perceived organizational support contributed 49.4% to employee performance. The conclusion of this study affirms that effective management of official travel budgets and the strengthening of organizational support are important factors in improving public-sector employee performance. These findings provide an empirical contribution to the development of public-sector management studies as well as practical implications for election supervisory institutions in strengthening the effectiveness of budget management and organizational support.